Spatiotemporal dynamics of high and low nucleic acid-content bacterial communities in Chinese coastal seawater: assembly process, co-occurrence relationship and the ecological functions - Hu, Wei; Zheng, Ningning; Zhang, Yadi; Bartlam, Mark; Wang, Yingying (Frontiers in Microbiology, 2023)
Studies of high nucleic acid-content (HNA) and low nucleic acid-content (LNA) bacterial communities are updating our view of their distributions and taxonomic composition. However, there are still large gaps in our knowledge of the composition, assembly processes, co-occurrence relationships and ecological functions of HNA and LNA bacterial communities. Here, using 16S rRNA gene amplicon sequencing, we investigated the spatiotemporal dynamics, assembly processes, co-occurrence relationships and ecological functions of HNA and LNA bacterial communities in the samples collected in summer and winter in Chinese coastal seas. The communities of HNA and LNA bacteria had clear spatiotemporal patterns and LNA bacteria was phylogenetically less diverse than HNA bacteria in both seasons. The distribution of HNA and LNA bacteria were significantly affected by the environmental factors and a significant seasonal-consistent distance-decay patterns were found in HNA and LNA bacteria. Furthermore, a quantitative assessment of ecological processes revealed that dispersal limitation, homogeneous selection exerted important roles in the community assembly of HNA and LNA bacteria. More importantly, we observed seasonality in the co-occurrence relationships: closer inter-taxa connections of HNA bacterial communities in winter than in summer and the opposite is true in the LNA bacterial communities. Some ecological functions, such as: phototrophy, photoautotrophy, oxygenic photoautotrophy, were different between HNA and LNA bacteria. These results provide a better understanding of spatiotemporal patterns, processes, and the ecological functions of HNA and LNA bacterial communities in Chinese coastal seawater.